2018
DOI: 10.1002/cctc.201800530
|View full text |Cite
|
Sign up to set email alerts
|

Batch versus Continuous Flow Performance of Supported Mono‐ and Bimetallic Nickel Catalysts for Catalytic Transfer Hydrogenation of Furfural in Isopropanol

Abstract: Furfural takes an important position in hemicelluloses biorefinery platforms. It can be converted into a wide range of chemicals. One important valorization route is the catalytic hydrogenation. Whereas molecular hydrogen is mostly used in industrial hydrogenation processes, recent studies also showed that alcohols can be used as reductants from which hydrides can be transferred catalytically to furfural. This process is often assisted by the formation of significant amounts of side products, in despite of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 29 publications
(83 reference statements)
1
41
0
Order By: Relevance
“…These results gave a clear hint that selective hydrogenation could be achieved by changing the reaction regime and conditions. Moreover, in the aforementioned work, two kinds of bimetallic catalysts, 5%Ni-15%W/C and 10%Ni-15%W/C, were also prepared [142]. Surprisingly, the activities of bimetallic catalysts were relatively lower than that of monometallic catalysts under the same reaction conditions, and poor reaction mass balance was noticed at a higher reaction temperature.…”
Section: Co Ni Based Catalystmentioning
confidence: 99%
“…These results gave a clear hint that selective hydrogenation could be achieved by changing the reaction regime and conditions. Moreover, in the aforementioned work, two kinds of bimetallic catalysts, 5%Ni-15%W/C and 10%Ni-15%W/C, were also prepared [142]. Surprisingly, the activities of bimetallic catalysts were relatively lower than that of monometallic catalysts under the same reaction conditions, and poor reaction mass balance was noticed at a higher reaction temperature.…”
Section: Co Ni Based Catalystmentioning
confidence: 99%
“…[40] We have designed and evaluated the reduction of acetophenone to 1-Phenyl ethanol as model substrate using sodium borohydride and water as a solvent. [41] - [42] 2. Experimental…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported that 1‐Phenyl ethanol is used as a flavoring agent, coloring agent in food additives, perfumery agent, and in pharmaceutical industries . We have designed and evaluated the reduction of acetophenone to 1‐Phenyl ethanol as model substrate using sodium borohydride and water as a solvent …”
Section: Introductionmentioning
confidence: 99%
“…Several drawbacks are present using this system: deactivation due to the sintering of active species; poisoning of the catalyst surface by coke formation; low selectivity of FOL; and high temperature and pressure. Up to now, several studies of selective hydrogenation of furfural to FOL have been performed in the liquid phase in batch reactors using different solvents, but very little attention has been paid to the process in a flow system [22][23][24][25][26]. To this aim, hydrogenation of furfural to FOL was studied in the presence of Co/SiO 2 catalyst in batch and in continuous flow reactors.…”
Section: Methodsmentioning
confidence: 99%